Deletion of Polyamine Transport Protein PotD Exacerbates Virulence in Glaesserella (Haemophilus) parasuis in the Form of Non-biofilm-generated Bacteria in a Murine Acute Infection Model. Issue 1 (1st January 2021) - Dai, Ke; Yang, Zhen; Ma, Xiaoyu; Chang, Yung-Fu; Cao, Sanjie; Zhao, Qin; Huang, Xiaobo; Wu, Rui; Huang, Yong; Xia, Jing; Yan, Qigui; Han, Xinfeng; et al.
ABSTRACT: Polyamines are small, polycationic molecules with a hydrocarbon backbone and multiple amino groups required for optimal cell growth. The potD gene, belonging to the ABC (ATP-binding cassette) transport system potABCD, encodes the bacterial substrate-binding subunit of the polyamine transport system, playing a pivotal role in bacterial metabolism and growth. The swine pathogen Glaesserella parasuis possesses an intact pot operon, and the studies presented here mainly examined the involvement of PotD in Glaesserella pathogenesis. A potD -deficient mutant was constructed using a virulent G. parasuis strain SC1401 by natural transformation; immuno-electron microscopy was used to identify the subcellular location of native PotD protein; an electron microscope was adopted to inspect biofilm and bacterial morphology; immunofluorescence technique was employed to study cellular adhesion, the levels of inflammation and apoptosis. The TSA++-pre-cultured mutant strain showed a significantly reduced adhesion capacity to PK-15 and MLE-12 cells. Likewise, we also found attenuation in virulence using murine models focusing on the clinical sign, H&E, and IFA for inflammation and apoptosis. However, when the mutant was grown in TSB++, virulence recovered to normal levels, along with a high level of radical oxygen species formation in the host. The expression of PotD could actively stimulate the production of ROS in Raw 264.7. Our data suggested that PotD from G. parasuis has a high binding potential to polyamine, and is essential for the full bacterial virulence within mouse models. However, the virulence of the potD mutant is highly dependent on its TSA++ culture conditions rather than on biofilm-formation.